PWE-044 Acute colon diverticulitis hospitalization trends in Veneto Region (Northeast Italy). Issue 2 (June 2019) - Saia, Mario; Caroli, Diego; Rosa-Rizzotto, Erik; Pilerci, Claudio; Lazzari, Franca De
Abstract : Introduction: Diverticular disease (DD) of the colon represents a common clinical condition affecting with high rate the population in developed countries. The rates of hospital admissions for Acute Colon Diverticulitis (ACD), the most important complication of DD, is progressively increased. The aim of our study is to describe the hospitalization trend for ACD in Veneto region, including in-hospital mortality, and the impact of specialistic admission hospital units as Gastroenterologic (GE) units. Methods: Data were obtained from the Veneto Region anonymous Hospital Discharge Record database from 2000 to 2017, in which diverticulitis of colon [ICD-9-CM code 562.11 and 562.13 (diverticulitis with and without mention of haemorrhage)] was the primary diagnosis. Standardized Hospitalization Rate (SHR) per five-year group was calculated and expressed per 100, 000 population. To evaluate the impact of admission hospital units on the outcome of ACD management we analyzed in-hospital mortality, need for surgery (NFS) and lenght of stay (LOS). Results: From 2000 to 2017 a total of 33, 249 hospitalization for AD were registered with an increasing rate from 0.30 to 0.46 for 1, 000 inhabitants (X 2 trend:514.182, p < 0.001;mean increase of 2.6% per year, p < 0.001)(FIG.1).Mean age was 66.1±28.4, higher in female (70.1±29.8 Vs.60.5±24.9;p<0.05) and the higher hospitalization rate (overall mean:0.39) was in female (0.43Vs.0.34;OR:1.30;CI95%:1.2–.32;p<0.001). SHR increased with age reaching the higher value in patients ≥85 years (162.43) with an increase of hospitalization over the study period for all class ages (p<0.001). Female showed an higher prevalence of hospitalization compared to men (OR:1.30;CI95%: 1.2–.32;p<0.001), and both genders presented an increasing trend, with a mean increase per year of 1.9% and 3.8% respectively (p<0.001). NFS was substantially stable (19.4%) while overall in-hospital mortality rate showed an important increase from 0.37 to 0.98 (p=0.037). Also LOS decreased significantly (-18%) from 9.8 to 8 days (p<0.001).73% of patients were overall admitted by surgical units with a steady increase for admission in medical ones from 22% to 34% and in particular in GE units where admission rose from 7% to 22% of overall admission of Medical Area. From the comparison between GE units and other medical area admissions, emerged that patients admitted in GE units have a not significantly lower (p>0.05) NFS rate (3.5%Vs.4.1%) and in-hospital mortality (0.3%Vs.1.4%), showing a significative lower LOS (7.1±2.2Vs.11±3.6;p<0.001). Conclusions: Results suggest that ACD is an emerging heath-care problem related to the rising of age. Through the years the NFS rate was stable with an increase of mortality. In this scenary GE units seem to be more efficiently obtaining a significative reduction of the cost management of ACD.